2012
DOI: 10.1007/s11224-012-9980-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-crystal/salt crystal structure disorder of trichloroacetic acid–N-methylurea complex with double system of homo- and heteronuclear O–H···O/N–H···O hydrogen bonds: X-ray investigation, ab initio and DFT studies

Abstract: The X-ray diffraction studies revealed disorder of a trichloroacetic acid-N-methylurea complex crystal structure, connected with a proton transfer via O-HÁÁÁO hydrogen bond. The observed structure corresponds to a co-existence of ionic (salt) and neutral (co-crystal) forms of the complex in the solid state in ratio 3:1, respectively. The geometrical analysis based on ab initio and density functional theory methods combined with the experimental research indicated that two different N-methylurea molecular confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…1 Many co-crystals and salts of NMU are reported in the literature. [2][3][4][5] Up to this study, the only known crystal structure of NMU is a stable form that was first proposed in 1933, 6 the structure was solved in 1976 by Huiszoon and Tiemessen 7 and lastly refined at 8 K by Chęcińska et al 8 NMU crystallizes in the orthorhombic system with the chiral (therefore non-centrosymmetric) space group P2 1 2 1 2 1 . Several studies investigated the enthalpies and entropies of fusion and solid-solid transition of urea, and its derivatives, including NMU where only the enthalpy of fusion of NMU has been reported.…”
Section: Introductionmentioning
confidence: 93%
“…1 Many co-crystals and salts of NMU are reported in the literature. [2][3][4][5] Up to this study, the only known crystal structure of NMU is a stable form that was first proposed in 1933, 6 the structure was solved in 1976 by Huiszoon and Tiemessen 7 and lastly refined at 8 K by Chęcińska et al 8 NMU crystallizes in the orthorhombic system with the chiral (therefore non-centrosymmetric) space group P2 1 2 1 2 1 . Several studies investigated the enthalpies and entropies of fusion and solid-solid transition of urea, and its derivatives, including NMU where only the enthalpy of fusion of NMU has been reported.…”
Section: Introductionmentioning
confidence: 93%
“…However, the strength of the mutual interaction is very weak because of its long distance and the small positive charge, therefore, this kind of interaction can be ignored. It was reported that the topology of the electron density at BCP is an indicator of the strength of intermolecular interations 39 . The hydrogen bonds in C-F1 and C-F3 have relatively large electron densities (0.0924 -0.0922 a.u.…”
Section: Topological Analysis Of Electronic Densitymentioning
confidence: 99%
“…However, in many instances, screening for cocrystals is preferable to screening for salts. For example, Salt formation is not possible when working with neutral molecules, as it requires at least one ionizable point on the API of interest [ 17 ]. Furthermore, screening for cocrystals is often preferable when working with weakly basic compounds due to the molecule’s pKa rendering it too low for the salt formation or forming a product with insufficient physical stability to provide an acceptable shelf-life [ 18 ].…”
Section: Introductionmentioning
confidence: 99%